Comparison of success criteria based on long-term symptoms and new-onset hypertension in mandibular advancement device treatment for obstructive sleep apnoea: observational cohort study. Issue 5 (8th May 2018) - Wee, Jee Hye; Lim, Jae Hyun; Gelera, January E; Rhee, Chae-Seo; Kim, Jeong-Whun
Abstract : Objective: To identify adequate criteria to determine the success or failure of mandibular advancement device (MAD) treatment for obstructive sleep apnoea (OSA) based on long-term symptoms and new-onset hypertension. Design: Observational cohort study. Setting: A tertiary care hospital setting in South Korea. Participants: Patients (age >18 years) who were diagnosed with OSA by a polysomnography (PSG) or Watch peripheral arterial tonometry (PAT), and who had been treated with MAD between January 2007 and December 2014 were enrolled. Primary and secondary outcome measures: Patients underwent PSG or Watch PAT twice; before and 3 months after the application of MAD. The patients were categorised into success and failure groups using seven different criteria. MAD compliance, witnessed apnoea and snoring, Epworth Sleepiness Scale score and occurrence of new-onset hypertension were surveyed via telephonic interview to determine the criteria that could identify success and failure of MAD. Results: A total of 97 patients were included. The mean follow-up duration was 60.5 months, and the mean apnoea–hypopnoea index (AHI) was 35.5/hour. Two of the seven criteria could significantly differentiate the success and failure groups based on long-term symptoms, including (1) AHI<10/hour with MAD and (2) AHI<10/hour and AHI reduction of >50% with MAD. Kaplan-Meier survival analysis showed that one criterion of AHI<15/hour with MAD could differentiate the success and failure groups based on new-onset hypertension (p=0.035). The receiver operating characteristic curve analysis indicated that the cut-off AHI for new-onset hypertension was 16.8/hour (71.4% sensitivity and 75.0% specificity). Conclusion: Our long-term follow-up survey for symptoms and new-onset hypertension suggested that some of the polysomnographic success criteria, that is, AHI<10/hour with MAD, AHI<10/hour and AHI reduction of >50% with MAD and AHI<15/hour with MAD may be useful in distinguishing the success group from failure one. Further prospective longitudinal studies are warranted to validate these criteria.